#### Answer

$-i$

#### Work Step by Step

Step 1: $i^{15}=i^{14+1}=i^{14}\times i$=$(i^{2})^{7}\times i$
Step 2: As $i^{2}=-1$,
$(i^{2})^{7}\times i=(-1)^{7}\times i=-1\times i=-i$

Chegg costs money, GradeSaver solutions are free!

Published by
Pearson

ISBN 10:
978-0-13-421743-7

ISBN 13:
978-0-13421-743-7

$-i$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.